من قضايا النقد الأدبي القديم في كتاب الأغاني لأبي الفرج الأصفهاني - بن طرية، عمر Ibn Tariah, Omar (جامعة قاصدي مرباح - ورقلة, 2018)
تروم هذه الورقة البحثية البحث في سفر نفيس من أسفار كتب الأخبار الفريدة من نوعها في موسوعيتها، واحتفائها بالتراث العربي في شتى مجالاته، فكان معينا لا ينضب ينهل منه الباحثون والدارسون، وينتقون من درره .ذلك السفر هو كتاب الأغاني لأبي الفرج الأصفهاني. وغايتنا من هذه الدراسة إماطة اللثام، ونفض الغبار عن هذا السفر، وإبراز بعضاً من فوائده الجمة، وبعثه من جديد. ومنهجنا في الدراسة، المنهج التاريخي وكذا المنهج الوصفي التحليلي.
This research paper aims to search for a rare book of unique books in its history, and to celebrate the Arab heritage in all its fields: there was an inexhaustible number of scholars, chosen from among its dhars. This trip is the book of songs for Abu Faraj al-Asfahani. The purpose of this study is revealed, and dust on this trip, and highlight some of the benefits of great, and resurrected. Our approach to the study, the historical approach, as well as the descriptive analytical approach.
Keywords: النقد الأدبي -- كتاب الأغاني -- الأصفهاني، أبي الفرج